Hydrogen evolution electrocatalyst as well as preparation method and application thereof

By loading hydrogen evolution electrocatalysts with high entropy alloys (such as MnFeCoNiRu) on nitrogen carbon support, using high entropy effect and metal-support interaction, the problem of high efficiency and economic catalyst design in the existing technology is solved, and high catalytic activity is achieved and Stable and low cost, suitable for promotion and application.

CN119265609APending Publication Date: 2025-01-07TIANFU YONGXING LAB +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411447938.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to design efficient and economical hydrogen evolution electrocatalysts, especially to maintain catalyst activity and stability while reducing the amount of precious metals. The structure of high-entropy alloy composite catalysts is complex and diverse, making it difficult to build clear and rich active sites. catalyst.

Method used

A high-entropy alloy (such as MnFeCoNiRu) is used to carry a nitrogen-carbon support as a hydrogen evolution electrocatalyst, and a high-entropy alloy composite catalyst is prepared by solvent thermal reaction and wet chemistry to form a nanoparticle structure, using high-entropy effect, lattice distortion effect and metal -Support interaction to improve catalytic activity and stability.

Benefits of technology

Achieve high-efficiency hydrogen evolution electrocatalyst with low cost and simple structure, with high catalytic activity and stability, exhibits performance comparable to commercial Pt/C catalysts in acidic media, and has no obvious current in the stability test of 4000 s attenuation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265609A_ABST
    Figure CN119265609A_ABST
Patent Text Reader

Abstract

The invention provides a hydrogen evolution electrocatalyst as well as a preparation method and application thereof, and relates to the technical field of catalytic materials. The hydrogen evolution electrocatalyst provided by the invention comprises a nitrogen-carbon carrier and a high-entropy alloy loaded on the nitrogen-carbon carrier. The hydrogen evolution electrocatalyst provided by the invention is simple in structure and low in cost, and has efficient catalytic activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and in particular to a hydrogen evolution electrocatalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of economy and science and technology, the modern chemical industry has made great achievements, but it has also brought about severe energy shortage and environmental pollution problems. Under the background of "dual carbon", hydrogen energy, as a recognized ideal clean energy, has broad market application prospects. Using renewable energy for electrochemical water splitting to produce hydrogen is a sustainable, pollution-free, and high-purity energy conversion method, and has become the focus of future hydrogen energy development (Angew. Chemie Int. Ed. 2020, 59, 20794-20812). However, as an important half-reaction in the process of water electrolysis, the hydrogen evolution reaction puts forward higher requirements for the precise synthesis and preparation of water electrolysis catalysts (Chem. Soc. Rev. 2020, 49, 3072-3106). The precious metal platinum (Pt) is currently the best performing hydrogen evolution catalyst, but its high cost restricts its large-scale use. Exploring and designing efficient and economical new catalysts to reduce the use of precious metals while improving the activity and stability of the catalyst is an important topic in the current green hydrogen production research, which has great scientific significance and practical value.

[0003] In recent years, high entropy alloys have attracted widespread attention from the scientific community as electrocatalysts (Matter 2023, 6, 1717-1751). Unlike known binary or ternary alloys, high entropy alloys usually contain 5 to 6 uniformly and randomly mixed metal elements, and generally present a single-phase structure. Due to the different sizes, chemical bonding and crystal structures of the metal components, as well as the random occupation of metal atoms in the lattice, mixing such a variety of metals will increase the lattice distortion in the crystal structure, reduce the diffusion rate of atoms, and the interaction between the elements may also bring unexpected synergistic catalytic effects (ACS Catal. 2020, 10, 11280-11306). Therefore, high entropy alloys can not only maintain good catalytic activity and stability, but also reduce the amount and cost of precious metals, and achieve diversified regulation of the adsorption free energy of reaction intermediates, which is an ideal catalyst for the future. However, the research on high entropy alloys in the field of electrocatalysis is still in its infancy, and it is still a challenge to achieve controllable synthesis of high entropy alloys.

[0004] At present, supported metal nanostructures are the most widely used catalyst structures, and the controllable synthesis of monodispersed nanocatalysts provides an ideal system for studying the catalytic reaction process (Chem. Rev. 2020, 120, 623-682). Therefore, the design of simple and controllable high-entropy alloy composite catalysts is the cornerstone of the application of high-entropy alloys in the field of electrocatalysis (Science. 2022, 376, 151). Domestic and foreign research groups have achieved certain results in the preparation of high-entropy alloy composite materials using the "top-down" physical fragmentation method or the "bottom-up" chemical reduction method (Sci. Rep. 2016, 6, 34213, Science. 2018, 359, 1489-1494), but the structure, stability and large-scale application of the obtained catalysts need to be further solved. Limited by the synthesis technology, the structure of high-entropy alloy composite catalysts is often complex and diverse, and how to construct catalysts with clear structures and abundant active sites is still a major problem. Summary of the invention

[0005] In view of this, an object of the present invention is to provide a hydrogen evolution electrocatalyst and a preparation method and application thereof. The hydrogen evolution electrocatalyst provided by the present invention has a simple structure, low cost, and high catalytic activity and stability.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The invention provides a hydrogen evolution electrocatalyst, comprising a nitrogen-carbon carrier and a high entropy alloy loaded on the nitrogen-carbon carrier.

[0007] Preferably, the high entropy alloy comprises a MnFeCoNiRu high entropy alloy.

[0008] Preferably, the high entropy alloy has the morphology of nanoparticles.

[0009] Preferably, the mass of the high entropy alloy accounts for 30-50% of the total mass of the hydrogen evolution electrocatalyst.

[0010] The present invention provides a method for preparing the hydrogen evolution electrocatalyst described in the above technical solution, comprising the following steps: The metal salt, polyvinyl pyrrolidone, benzyl alcohol and aniline are mixed and subjected to a solvothermal reaction to obtain a high entropy alloy; The ZIF-8 powder was pyrolyzed to obtain a nitrogen-carbon carrier; The high entropy alloy, the nitrogen-carbon carrier and methanol are mixed, and wet chemical impregnation is performed, and the obtained precipitate is heat-treated to obtain a hydrogen evolution electrocatalyst.

[0011] Preferably, the temperature of the solvothermal reaction is 160-200° C.; the time of the solvothermal reaction is 10-14 h.

[0012] Preferably, the pyrolysis is carried out under a protective atmosphere; the pyrolysis temperature is 900-1000°C; the pyrolysis time is 2-5h; and the heating rate from room temperature to the pyrolysis temperature is 2-10°C / min.

[0013] Preferably, the mass ratio of the high entropy alloy to the nitrogen-carbon carrier is 1:1-3.

[0014] Preferably, the heat treatment is carried out under a protective atmosphere; the temperature of the heat treatment is 200-400°C; the time of the heat treatment is 1-3 hours; the heating rate from room temperature to the temperature of the heat treatment is 2-10°C / min.

[0015] The present invention provides the use of the hydrogen evolution electrocatalyst described in the above technical solution or the hydrogen evolution electrocatalyst prepared by the preparation method described in the above technical solution in hydrogen production by electrolysis of water.

[0016] The present invention provides a hydrogen evolution electrocatalyst, comprising a nitrogen-carbon carrier and a high entropy alloy supported on the nitrogen-carbon carrier. In the present invention, the high entropy alloy is formed by solid solution of multiple elements, has a clear crystal structure, uniform element distribution, and has high entropy effect, lattice distortion effect, etc. The nitrogen-carbon material provides an anchoring position for the high entropy alloy, and the nanoparticles are uniformly dispersed on the carrier, with a clear and stable structure and abundant active sites.

[0017] The present invention utilizes the high entropy effect, lattice distortion effect, hysteresis diffusion effect, cocktail effect of high entropy alloy and metal-support interaction of composite materials to enable the hydrogen evolution electrocatalyst to have efficient catalytic activity and stability. The hydrogen evolution electrocatalyst provided by the present invention has low cost and simple structure and is suitable for promotion and application. The results of the examples show that the hydrogen evolution electrocatalyst provided by the present invention exhibits high catalytic activity and stability in an acidic medium. The hydrogen evolution electrocatalyst has a high catalytic activity and stability at -10 mA·cm -2 The overpotential at a current density of only -74 mV is comparable to that of commercial standard Pt / C catalysts; no obvious current decay occurs after a 4000 s stability test.

[0018] The present invention provides a method for preparing the hydrogen evolution electrocatalyst described in the above technical solution. The preparation method provided by the present invention has the advantages of being novel, controllable and simple to operate, and the method has great economic advantages and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The synthesis flow chart of the hydrogen evolution electrocatalyst in the present invention; Figure 2 Characterize the morphology of the high entropy alloy in the present invention; Figure 3 Characterize the morphology of the hydrogen evolution electrocatalyst in the present invention; Figure 4 Phase analysis of the hydrogen evolution electrocatalyst in the present invention; Figure 5 The results of the electrocatalytic hydrogen evolution reaction performance experiment in the present invention; Figure 6 The results are experimental results of the stability of the electrocatalytic hydrogen evolution reaction in the present invention. DETAILED DESCRIPTION

[0020] The invention provides a hydrogen evolution electrocatalyst, comprising a nitrogen-carbon carrier and a high entropy alloy loaded on the nitrogen-carbon carrier.

[0021] The hydrogen evolution electrocatalyst provided by the present invention comprises a nitrogen-carbon carrier. In the present invention, the nitrogen-carbon carrier is preferably a nitrogen-doped carbon material derived from the pyrolysis of ZIF-8. In the present invention, the nitrogen-carbon carrier is preferably a porous structure. In the present invention, the specific surface area of ​​the nitrogen-carbon carrier is preferably 760-780 m 2 / g, more preferably 770 m 2 / g; the pore volume is preferably 0.35~0.45 cm 3 / g, more preferably 0.4 cm 3 / g; the pore diameter is preferably 2.1~3.8 nm, more preferably 3.3 nm.

[0022] The hydrogen evolution electrocatalyst provided by the present invention comprises a high entropy alloy supported on the nitrogen-carbon carrier. In the present invention, the high entropy alloy preferably comprises a MnFeCoNiRu high entropy alloy. The present invention uses cheap metals and ruthenium in combination as high entropy alloys, reduces the amount of precious metals used, and reduces costs.

[0023] In the present invention, the morphology of the high entropy alloy is preferably nanoparticles; the particle size of the high entropy alloy is preferably <5 nm, more preferably 4 nm.

[0024] In the present invention, the mass of the high entropy alloy accounts for preferably 30-50% of the total mass of the hydrogen evolution electrocatalyst, and more preferably 37.5%.

[0025] The present invention provides a method for preparing the hydrogen evolution electrocatalyst described in the above technical solution, comprising the following steps: The metal salt, polyvinyl pyrrolidone, benzyl alcohol and aniline are mixed and subjected to a solvothermal reaction to obtain a high entropy alloy; The ZIF-8 powder was pyrolyzed to obtain a nitrogen-carbon carrier; The high entropy alloy, the nitrogen-carbon carrier and methanol are mixed, and wet chemical impregnation is performed, and the obtained precipitate is heat-treated to obtain a hydrogen evolution electrocatalyst.

[0026] The present invention mixes a metal salt, polyvinyl pyrrolidone, benzyl alcohol and aniline, and performs a solvothermal reaction to obtain a high entropy alloy. In the present invention, the metal salt is preferably a metal acetylacetonate. In the present invention, the metal salt preferably includes a manganese salt, an iron salt, a cobalt salt, a nickel salt and a ruthenium salt; the molar ratio of the manganese salt, the iron salt, the cobalt salt, the nickel salt and the ruthenium salt is preferably 1:1:1:1:1. In the present invention, the molecular weight of the polyvinyl pyrrolidone is preferably 8000 to 12000, more preferably 8000. In the present invention, the mixing is preferably carried out under ultrasonic conditions. In the present invention, the mixing of the metal salt, polyvinyl pyrrolidone, benzyl alcohol and aniline preferably includes: dissolving the metal salt in part of the benzyl alcohol to obtain a metal salt solution; dissolving the polyvinyl pyrrolidone in the remaining benzyl alcohol to obtain a polyvinyl pyrrolidone solution; mixing the metal salt solution and the polyvinyl pyrrolidone solution, and adding aniline. In the present invention, the mass ratio of the metal salt to polyvinyl pyrrolidone is preferably 2 to 4:5, more preferably 2:5. In the present invention, the concentration of the metal salt solution is preferably 0.05 to 0.2 mmol / mL, more preferably 0.1 to 0.15 mmol / mL. In the present invention, the concentration of the polyvinyl pyrrolidone solution is preferably 10 to 30 mg / mL, more preferably 20 to 25 mg / mL. In the present invention, the mass ratio of the metal salt to aniline is preferably 1:1.58 to 3.15, more preferably 1:3.15. In the present invention, the role of the polyvinyl pyrrolidone is a surfactant, the role of the benzyl alcohol is a solvent and a dispersant, and the role of the aniline is a solvent and an auxiliary agent.

[0027] In the present invention, the temperature of the solvothermal reaction is preferably 160-200°C, more preferably 180°C; the time of the solvothermal reaction is preferably 10-14h, more preferably 12h. In the present invention, during the solvothermal reaction, the five metal atoms are randomly distributed and highly solid-dissolved together to form a single crystal structure.

[0028] In the present invention, after the solvent thermal reaction, the obtained reaction product is preferably washed and dried in sequence to obtain a high entropy alloy. In the present invention, the washing liquid used for the washing is preferably acetone. In the present invention, the drying temperature is preferably 60° C., and the drying time is preferably 24 hours.

[0029] In a specific embodiment of the present invention, the high entropy alloy presents a uniform, monodispersed morphology, and the particle size is less than 5 nm, which is conducive to exposing more active sites.

[0030] The present invention pyrolyzes ZIF-8 powder to obtain a nitrogen-carbon carrier. In the present invention, the preparation method of the ZIF-8 powder preferably includes: mixing 2-methylimidazole, zinc nitrate and methanol, standing, and obtaining ZIF-8 powder after solid-liquid separation. In the present invention, the zinc nitrate is preferably zinc nitrate hexahydrate. In the present invention, the mixing is preferably carried out under ultrasonic conditions. In the present invention, the mixing of 2-methylimidazole, zinc nitrate and methanol preferably includes: dissolving 2-methylimidazole in part of methanol to obtain a 2-methylimidazole solution; dissolving zinc nitrate in the remaining methanol to obtain a zinc nitrate solution; and mixing the 2-methylimidazole solution and the zinc nitrate solution. In the present invention, the mass ratio of 2-methylimidazole to zinc nitrate is preferably 1312~1161:1116~1069, more preferably 1161:1069. In the present invention, the concentration of the 2-methylimidazole solution is preferably 58.05~116.1 mg / mL, more preferably 77.4~100 mg / mL; the concentration of the zinc nitrate solution is preferably 53.45~106.9 mg / mL, more preferably 71.3~100 mg / mL. In the present invention, the standing temperature is preferably room temperature; the standing time is preferably 10~14h, more preferably 12h. In the present invention, during the standing process, Zn ions and bridged organic ligands are interconnected by self-assembly to form a crystalline porous material with a periodic network structure. In the present invention, the solid-liquid separation is preferably centrifugal separation. In the present invention, after the solid-liquid separation, the obtained precipitate is preferably dried to obtain ZIF-8 powder. In the present invention, the drying temperature is preferably 60°C, and the drying time is preferably 24h.

[0031] In the present invention, the pyrolysis is preferably carried out under a protective atmosphere, more preferably in a nitrogen atmosphere; the pyrolysis temperature is preferably 900-1000°C, more preferably 950-970°C; the pyrolysis time is preferably 2-5h, more preferably 3-4h; the heating rate from room temperature to the pyrolysis temperature is preferably 2-10°C / min, more preferably 5-7°C / min.

[0032] In the present invention, during the pyrolysis process, Zn is removed from the framework material, and the structure remains unchanged, thereby obtaining a porous nitrogen-carbon carrier.

[0033] After obtaining the high entropy alloy and the nitrogen-carbon carrier, the present invention mixes the high entropy alloy, the nitrogen-carbon carrier and methanol, performs wet chemical impregnation, and heat treats the obtained precipitate to obtain a hydrogen evolution electrocatalyst. In the present invention, the mass ratio of the high entropy alloy and the nitrogen-carbon carrier is preferably 1:1~3, more preferably 1:1.6~2. In the present invention, the mixing is preferably carried out under ultrasonic conditions. In the present invention, the mixing of the high entropy alloy, the nitrogen-carbon carrier and methanol preferably includes: mixing the high entropy alloy and part of the methanol to obtain a high entropy alloy dispersion; mixing the nitrogen-carbon carrier and the remaining methanol to obtain a nitrogen-carbon carrier dispersion; mixing the high entropy alloy dispersion and the nitrogen-carbon carrier dispersion. In the present invention, the concentration of the high entropy alloy dispersion is preferably 1.0~2.0 mg / mL, more preferably 1.7 mg / mL; the concentration of the nitrogen-carbon carrier dispersion is preferably 1.0~2.0 mg / mL, more preferably 1.7 mg / mL.

[0034] In the present invention, the wet chemical impregnation preferably includes ultrasound and heat preservation performed in sequence; the power of the ultrasound is preferably 40~100W, more preferably 100W; the time of the ultrasound is preferably 1~3h, more preferably 2h; the temperature of the ultrasound is preferably room temperature. In the present invention, the temperature of the heat preservation is preferably 40~80℃, more preferably 60℃; the time of the heat preservation is preferably 10~14h, more preferably 12h. In the present invention, during the wet chemical impregnation process, the high entropy alloy nanoparticles are fully contacted and adsorbed with the nitrogen-carbon carrier.

[0035] In the present invention, after the wet chemical impregnation, solid-liquid separation is preferably performed to obtain a precipitate. In the present invention, the solid-liquid separation is preferably centrifugal separation.

[0036] In the present invention, the precipitate preferably further comprises drying before the heat treatment. In the present invention, the drying temperature is preferably 60° C., and the drying time is preferably 24 hours.

[0037] In the present invention, the heat treatment is preferably carried out under a protective atmosphere, more preferably in a nitrogen atmosphere; the temperature of the heat treatment is preferably 200-400°C, more preferably 280-300°C; the time of the heat treatment is preferably 1-3h, more preferably 2h; the heating rate from room temperature to the temperature of the heat treatment is preferably 2-10°C / min, more preferably 5-7°C / min. In the present invention, during the heat treatment, high entropy alloy nanoparticles migrate at high temperature and are captured and anchored by defect sites rich in nitrogen and carbon carriers.

[0038] In the present invention, cooling is preferably performed after the heat treatment to obtain a hydrogen evolution electrocatalyst.

[0039] The present invention provides the use of the hydrogen evolution electrocatalyst described in the above technical solution or the hydrogen evolution electrocatalyst prepared by the preparation method described in the above technical solution in the production of hydrogen by electrolysis of water. In the present invention, the application is preferably carried out in an acidic environment. In the present invention, the electrolyte used in the production of hydrogen by electrolysis of water is preferably a 0.5 mol / L H2SO4 solution. The hydrogen evolution electrocatalyst provided by the present invention exhibits high catalytic activity in the hydrogen evolution reaction.

[0040] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art. The molecular weight of polyvinyl pyrrolidone used in the examples is 8,000.

[0042] Example 1

[0043] like Figure 1 As shown, this embodiment provides a method for preparing a high-efficiency hydrogen evolution electrocatalyst, and the steps are as follows: Step 1.1, weigh 0.1 mmol each of manganese acetylacetonate, iron acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate and ruthenium acetylacetonate, add 5 mL of benzyl alcohol, and dissolve by ultrasonication.

[0044] Step 1.2, weigh 400 mg of polyvinyl pyrrolidone, add 20 mL of benzyl alcohol, and dissolve by ultrasonication.

[0045] Step 1.3, mix the solutions obtained in steps 1.1 and 1.2, add 0.5 mL of aniline and continue ultrasonication for 30 min.

[0046] Step 1.4, transfer the solution obtained in step 1.3 to a Teflon reactor and perform a solvothermal reaction at 180°C for 12 h.

[0047] Step 1.5, taking out the product after the reaction, washing it with acetone, and drying it at 60° C. for 24 h to obtain MnFeCoNiRu high entropy alloy nanoparticles. Figure 2 To characterize the morphology of MnFeCoNiRu high entropy alloy nanoparticles, Figure 2 As shown, the MnFeCoNiRu high entropy alloy nanoparticles present a uniform and monodispersed morphology, and the particle size is <5 nm, which is conducive to exposing more active sites.

[0048] In step 2.1, weigh 1161 mg of 2-methylimidazole and add 15 mL of methanol to fully dissolve it.

[0049] Step 2.2, weigh 1069 mg of zinc nitrate hexahydrate, add 15 mL of methanol and dissolve thoroughly.

[0050] Step 2.3, mix the solutions obtained in steps 2.1 and 2.2 evenly, and let stand for 12 h after ultrasonication.

[0051] Step 2.4, centrifuge the product obtained in step 2.3, and dry the precipitate at 60°C for 24 hours.

[0052] Step 2.5, placing the powder obtained in step 2.4 in a flowing nitrogen atmosphere, heating to 950°C at a rate of 5°C / min and maintaining for 3 h, the material changes from white to black, and a nitrogen-carbon carrier is obtained. The specific surface area of ​​the nitrogen-carbon carrier prepared in this example is 770 m 2 / g, pore volume 0.4 cm 3 / g, and the pore size is 3.3 nm.

[0053] Step 3.1, weigh 50 mg of the MnFeCoNiRu high entropy alloy, add 30 mL of methanol to obtain a MnFeCoNiRu high entropy alloy dispersion; weigh 50 mg of the nitrogen-carbon carrier, add 30 mL of methanol to obtain a nitrogen-carbon carrier dispersion; mix the MnFeCoNiRu high entropy alloy dispersion and the nitrogen-carbon carrier dispersion evenly, ultrasonicate at room temperature for 2 h, and then keep warm at 60°C for 12 h.

[0054] Step 3.2, centrifuge the product obtained in step 3.1, and dry the precipitate at 60°C for 24 hours.

[0055] Step 3.3, placing the powder obtained in step 3.2 in a flowing nitrogen atmosphere, heating to 300°C at a rate of 5°C / min and maintaining for 2 h, and obtaining a hydrogen evolution electrocatalyst after cooling.

[0056] like Figure 3 and Figure 4 As shown, morphological characterization and phase analysis of the hydrogen evolution electrocatalyst showed that the MnFeCoNiRu high entropy alloy nanoparticles and the nitrogen-carbon carrier were successfully composited through interaction, the metal elements remained evenly distributed, and the composite catalyst presented a single phase structure.

[0057] 4 mg of the hydrogen evolution electrocatalyst prepared in Example 1 and 10 μL of Nafion solution (5 wt%) were added to 1 mL of a mixed solution of deionized water and ethanol (the volume ratio of deionized water to ethanol was 1:2) and ultrasonically treated for 30 min to obtain a well-dispersed catalyst slurry (catalyst concentration was 4 mg mL-1 HER test uses a three-electrode system, with a graphite rod as the counter electrode and a saturated calomel electrode as the reference electrode. 10 μL of the catalyst slurry prepared above is dropped on a surface area of ​​0.196 cm 2 The working electrode was prepared on a glassy carbon (GC) electrode with a catalyst loading of 0.102 mg cm -2 0.5 mol / L H2SO4 solution was used as the reaction electrolyte. The scan rate of the linear sweep voltammetry (LSV) experiment was 10 mV s -1 .Depend on Figure 5 It can be seen that in the acidic environment of 0.5 mol / L H2SO4 solution, the hydrogen evolution electrocatalyst (high entropy alloy hydrogen evolution catalyst) prepared by the present invention is -10 mA·cm -2 The overpotential at a current density of only -74 mV is comparable to that of commercial standard Pt / C catalysts; the hydrogen evolution electrocatalyst prepared by the present invention exhibits Pt / C-like electrocatalytic hydrogen evolution activity, which is attributed to the high entropy alloy nanoparticles uniformly distributed on the nitrogen-carbon carrier, which fully exposes the active sites of the catalyst. In addition, the synergy of the high entropy alloy components in the hydrogen evolution electrocatalyst and the interaction between the metal and the carrier make the catalyst exhibit excellent intrinsic activity.

[0058] The constant current test was carried out in 0.5 mol / L H2SO4 solution at -10 mA cm −2 The catalyst stability was evaluated at a constant current density of 1.3 Å, and no stirring or N2 purge was required during the reaction. Figure 6 It shows that after 4000 s of stability test, there is no obvious current decay, which indicates that the hydrogen evolution electrocatalyst prepared by the present invention has good stability.

[0059] Benefiting from the synergy of multiple elements and the interaction between metal and support, the hydrogen evolution electrocatalyst prepared by the present invention exhibits high electrocatalytic hydrogen evolution reaction activity and stability in an acidic environment.

[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A hydrogen evolution electrocatalyst, characterized in that The invention comprises a nitrogen-carbon carrier and a high entropy alloy supported on the nitrogen-carbon carrier.

2. The hydrogen evolution electrocatalyst according to claim 1, characterized in that The high entropy alloy includes a MnFeCoNiRu high entropy alloy.

3. The hydrogen evolution electrocatalyst according to claim 1, characterized in that The high entropy alloy has the morphology of nanoparticles.

4. The hydrogen evolution electrocatalyst according to any one of claims 1 to 3, characterized in that The mass of the high entropy alloy accounts for 30-50% of the total mass of the hydrogen evolution electrocatalyst.

5. The method for preparing the hydrogen evolution electrocatalyst according to any one of claims 1 to 4, comprising the following steps: The metal salt, polyvinyl pyrrolidone, benzyl alcohol and aniline are mixed and subjected to a solvothermal reaction to obtain a high entropy alloy; The ZIF-8 powder was pyrolyzed to obtain a nitrogen-carbon carrier; The high entropy alloy, the nitrogen-carbon carrier and methanol are mixed, and wet chemical impregnation is performed, and the obtained precipitate is heat-treated to obtain a hydrogen evolution electrocatalyst.

6. The preparation method according to claim 5, characterized in that: The temperature of the solvent thermal reaction is 160-200° C.; the time of the solvent thermal reaction is 10-14 hours.

7. The preparation method according to claim 5, characterized in that: The pyrolysis is carried out under a protective atmosphere; the pyrolysis temperature is 900-1000°C; the pyrolysis time is 2-5h; and the heating rate from room temperature to the pyrolysis temperature is 2-10°C / min.

8. The preparation method according to claim 5, characterized in that: The mass ratio of the high entropy alloy to the nitrogen-carbon carrier is 1:1-3.

9. The preparation method according to claim 5, characterized in that: The heat treatment is carried out under a protective atmosphere; the temperature of the heat treatment is 200-400°C; the time of the heat treatment is 1-3h; the heating rate from room temperature to the temperature of the heat treatment is 2-10°C / min.

10. Use of the hydrogen evolution electrocatalyst according to any one of claims 1 to 4 or the hydrogen evolution electrocatalyst prepared by the preparation method according to any one of claims 5 to 9 in hydrogen production by electrolysis of water.

Citation Information

Cited By

  • Synthesis method of nitrogen-doped carbon-coated multi-metal nanosheet array and water electrolysis application of nitrogen-doped carbon-coated multi-metal nanosheet array

    CN119956409A